El den y el cat: aproximaciones a un mismo idioma cajamarquino - Torres Menchola, Denis (Pontificia Universidad Católica del Perú, 2024)
The objective of this paper is to offer an insight on two hypothetical languages from the department of Cajamarca, Peru, named den and cat, whose existence was postulated based on toponymy. From a georeferenced database, a set of toponyms from the department was selected, in which the segments <den> and their variants, associated to the den language, and <cat> and <can> and their variants, linked to the language cat, were identified. The names were cartographically visualized using a geographic positioning system that allowed their exact location based on the use of georeferenced coordinates. The distribution of the toponyms with the three segments allows to assert with confidence that they are part of the same linguistic entity.

El objetivo del presente artículo es exponer una perspectiva acerca de dos lenguas hipotéticas del departamento de Cajamarca, Perú, denominadas den y cat, cuya existencia fue postulada a partir de la toponimia. De una base de datos georreferenciados, se tomó un conjunto de topónimos del departamento en los que aparecían los segmentos <den> y sus variantes, atribuidos a la lengua den; y <cat> y <can> y sus variantes, atribuidos a la lengua cat. Los nombres se visualizaron cartográficamente mediante un sistema de posicionamiento geográfico que permitía su ubicación exacta en virtud del empleo de coordenadas georreferenciadas. La distribución de los topónimos con los tres segmentos permite plantear con solidez que forman parte de una misma entidad idiomática.
Den and Cat: Approaches to One Single Cajamarcan Language
Keywords: Toponymy; Den; Cat; Cartographic visualization; Toponimia; Den; Cat; Visualización cartográfica; https://purl.org/pe-repo/ocde/ford#6.02.06